Avaliação energética e de desempenho de frango de corte, numa agroindústria avícola com sistema automático de aquecimento a gás e a lenha - Funck, Sandro Ricardo (2006)
This work had as objective the assembly of a system automated for evaluation of the consumption of fuel in agricultural tractors, in the utilization of biodiesel in diverse mixtures diesel/biodiesel for the accomplishment of testing, without the utilization of the tank of the tractor. The system was projected and mounted on the UNIOESTE Cascavel - PR in partnership with the UTFPR Medianeira PR. The system is composed for two auxiliary tanks confectioned in stainless steel 306 with capacity for 6 each liters, the which serve of deposit for the mixture diesel/biodiesel utilized in the accomplishment of field assays. The selection of the fuel flow is made by a selector key tripolar that is responsible by the drive of the valves solenoids 3/2 ways, being these responsible by the addressing of the flow of tanks 1, 2 and of the tractor for the measurer of flow and this for the injector bomb and the return for the corresponding tank utilized. Were confectioned two boards, a for the activate of the valves solenoids and another for the flows meters and temperature sensor. To monitoring of the consumption of fuel is carried out by two sets containing: a temperature sensor mounted in series with flow meter, being the data collected for a acquisition data system of the type Microlloger model CR23X for the accomplishment of the calculations of the fuel consumption. The testing of laboratory showed satisfactory results in the selection of the stream of feed and return for all the positions in the selector key tripolar. For the accomplishment of the testing field, the system was installed in an agricultural tractor Massey Ferguson model 5285 - 4 x 2 TDA tractioning an chisel plow with 7 rod in 5 mixtures of diesel/biodiesel, presenting satisfactory result for all the mixtures selected.